Non-antibiotic possibilities in prevention and treatment of calf diarrhoea - Smulski Sebastian (Sciendo, 2020)
Due to increasing bacterial antibiotic resistance and the consumers’ tendency to choose organic products, cattle farmers are interested in alternative methods of calf diarrhoea treatment. This is a major challenge for veterinarians. Few methods of non-antibiotic treatment that bring satisfactory results have been reported in the related literature so far. In this article, the authors compare different non-antibiotic methods of diarrhoea prevention and treatment in calves. Among the alternatives discussed are herbs, probiotics, prebiotics and synbiotics, lactoferrin, and bacteriophages. It was found that the best results could be achieved through the use of pro-, pre- and synbiotics. However, the authors would like to point out that with the expansion of knowledge about the practical use of broad-scale bacteriophages, they could be the best alternative to antibiotics.